2006
DOI: 10.1177/0091270006293754
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Drug Monitoring of Antidepressants and Cytochrome P450 Genotyping in General Practice

Abstract: In the psychiatric setting, therapeutic drug monitoring and genotyping for cytochrome P450 (CYP) polymorphisms help to ensure and maintain therapeutic drug levels. In this study, the authors extended the therapeutic drug monitoring and genotyping protocol routinely used in their psychiatric clinic to primary care patients treated with antidepressants. They examined the variation in serum concentrations and assessed the role of CYP polymorphisms, wrong dosing, and noncompliance in deviating serum concentrations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 41 publications
0
16
0
1
Order By: Relevance
“…Co-prescription of psychotropic and other CNS-acting medications creates an especially high risk for drug-drug interactions in that these agents are often transported and metabolized by the same polymorphic enzymes. When antidepressant drug levels were measured in the blood of patients in a general practice setting, Kootstra et al found that 56% of patients were outside of the therapeutic range [26]. This suggests that variability in exposure may be driving the high degree of outcome variability with this class of medications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Co-prescription of psychotropic and other CNS-acting medications creates an especially high risk for drug-drug interactions in that these agents are often transported and metabolized by the same polymorphic enzymes. When antidepressant drug levels were measured in the blood of patients in a general practice setting, Kootstra et al found that 56% of patients were outside of the therapeutic range [26]. This suggests that variability in exposure may be driving the high degree of outcome variability with this class of medications.…”
Section: Discussionmentioning
confidence: 99%
“…However, although this may seem to be an infrequent event, this would represent nearly 200,000 patients over the age of 65 in the US alone based on 2012 census estimates. New practices are now available that target improved utilization of drug interaction data [4, 26]. …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, an optimal early antidepressant dosing strategy may have to comprise several endogenic and exogenic factors, possibly including age, body composition, concomitant medication, food components and/or smoking habit. 42 With regard to body composition, IMI doses applied by the physician are not generally based on the patient's sex, weight or body surface area. 7,43 In line with this, there was no significant contribution of body weight or sex to the prediction of IMI þ DESI plasma concentration, IMI dose at steady state or IMI dose requirement in our present multivariate linear regression model.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in some secondary psychiatric care facilities in the Netherlands, genotyping is already implemented as care as usual [23]. However, no information concerning the cost-effectiveness of routine genotyping at the start of nortriptyline treatment among depressed hospitalized patients is available.…”
Section: Introductionmentioning
confidence: 99%